The state-trait anger expression and family values in native Greeks, immigrants and remigrants - Γ. Μπεζεβέγκης Ηλίας; Ντάλλα Μαρίνα; Γκαρή Αικατερίνη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF